Pengembangan Media Powerpoint Interaktif pada Pembelajaran IPA untuk Meningkatkan Minat Belajar Siswa Sekolah Dasar - Abdul Wahid; Nur Dewi Wulandari; Nur Afni; Fani Arfaita Istiqamah; Siti Syahraeni (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2026)
This study aims to develop interactive PowerPoint learning media in science learning to improve elementary school students’ learning interest. The research employed the Research and Development (RD) method using the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The subjects of this study were 20 second-grade students of SD Inpres Borong Jambu II. The research procedure began with an analysis of learning needs, followed by media design, product development, implementation in the learning process, and evaluation of the media’s effectiveness. Data collection techniques included observation, validation questionnaires from material and media experts, interviews with teachers, and student response questionnaires to assess the effectiveness and attractiveness of the learning media. Data analysis was conducted using descriptive quantitative analysis to process questionnaire and observation results, while qualitative analysis was used to interpret interview data and participants’ responses. The validation and trial data were analyzed to determine the feasibility and success of the media development in improving students’ learning interest. The results of the material and media expert validations indicated that the developed media was highly feasible for use. Trials conducted with students showed an increase in learning interest from 60 to 85 and science learning outcomes from 55 to 88. This media helped students understand abstract concepts through interactive visualization and encouraged active participation in classroom learning. Therefore, interactive PowerPoint media can make science learning more active and innovative while improving elementary school students’ interest and learning outcomes.